DAMPAK LITERASI KEUANGAN TERHADAP MINAT INVERTASI PADA PASAR MODAL DIKALANGAN GENERASI MILENIAL - Annisa Wulandari; Indahwati, Rini (Politeknik Negeri Medan, 2024)
The number of investors in the capital market in Indonesia is still quite low, indicated by the low number of investors in the capital market sector when compared to other financial products and services. This is because the public's understanding and knowledge is not yet well literate regarding investment in the capital market. Knowledge and skills regarding investment will increase interest and motivation in investing. This research aims to determine the impact of financial literacy on investment interest in the capital market among the millennial generation. The population in this study were Medan State Polytechnic students who had an interest in investing. Based on sampling calculations using the probability sampling method with the Slovin formula, a sample of 63 respondents was obtained. Data collection techniques through questionnaires using simple linear regression analysis. Instrument trials were analyzed using validity tests and reliability tests. The results of this research show that financial literacy has a significant effect on investment interest among the millennial generation.